Kidney Injury Following Ibuprofen and Acetaminophen: A Real-World Analysis of Post-Marketing Surveillance Data - Shao, Qi-hui; Yin, Xue-dong; Liu, Hong-xia; Zhao, Bin; Huang, Jian-quan; Li, Zhi-ling (Frontiers in Pharmacology, 2021)
Background Although kidney injury has been reported as a serious adverse effect in patients treated with ibuprofen or acetaminophen (APAP), there are still few real-world studies to compare the specific differences in the adverse effects of nephrotoxicity. Methods Disproportionality analysis and Bayesian analysis were devoted to data-mining of the suspected kidney injury after using ibuprofen and APAP based on the FDA’s Adverse Event Reporting System (FAERS) from January 2004 to March 2021. The times to onset, fatality, and hospitalization rates of ibuprofen-associated kidney injury and APAP-associated kidney injury were also investigated. Results 2453 reports of ibuprofen-associated kidney injury and 1288 reports of APAP-associated kidney injury were identified. Ibuprofen appeared to affected more middle-aged patients than elderly ones (27.76% vs 16.53%) while APAP appeared to affected more young patients than middle-aged patients (45.24% vs 29.10%) and elderly patients were fewer (13.99%). Compared to ibuprofen, APAP had the higher association with renal injury based on the higher reporting odds ratio (ROR = 2.45, 95% two-sided CI = 2.36-2.56), proportional reporting ratio (PRR = 2.39, χ2 = 2002.94) and empirical Bayes geometric mean (EBGM = 2.38, 95% one-sided CI = 2.3). In addition, APAP-associated kidney injury had earlier onset (32.74 days vs 115.82 days, p<0.0001) and a higher fatality rate (44.43% vs 7.36%, p < 0.001) than those of ibuprofen-associated kidney injury. Conclusions The analysis of FAERS data provides a more accurate profile on the incidence and prognosis of kidney injury after ibuprofen and acetaminophen treatment, enabling continued surveillance and timely intervention in patients at risk of kidney injury using these drugs.